Real Africa and Africa dreamt in contemporary Sub-Saharian novels : The example of "Balbala" and "Aux Etats-Unis d'Afrique" written by Abdourahman Ali Waberi ; "Le Baobab Fou" and "La Pièce d'or" written by Ken Bugul - (:unkn) unknown (My University, 2016)
Our study which is focused on the French literature is titled: Real Africa and Africa dreamt in contemporary Sub-Saharan novels. The example of: “Balbala" and "Aux Etats-Unis d'Afrique" written by Waberi (A.A.); "Le Baobab fou" and "La Pièce d'or" written by Ken Bugul. The importance of this research consists in observing the process of Africa's reconfiguration in the works mentioned above. It is not only about analyzing the real, dreamt, or ambivalent Africa, it is about observing textual methods for which the passage from a real Africa to a dreamt Africa is possible and, how this back and forth of a universe that is lead in a third space can be perceived as alternative Africa that the authors of these texts aspire. Furthermore, these texts become the diagnostic tools of the failings of the society and equally help to provide preemptive solutions on the operation of the continent. To conduct this study, we used a double methodology such as the textual poetic of Gerard Genette and the interpretative semiotic revisited by Louis Hebert. At the end of ours analyses we keep in mind that in these texts the authors express an alternative Africa. They present it as she is, and also the way they would like it to be. But such vision of the world isn't it a simple utopia which falls under the unattainable ?
Keywords: African Research